Peripheral blood kinetics following total body irradiation and allogeneic hematopoietic stem cell transplantation: timing matters: brief communication - Dejonckheere, Cas S.; Böhner, Alexander M. C.; Schmitz, Eva; Holderried, Tobias A. W.; Schmeel, Leonard C.; Brossart, Peter; Giordano, Frank Anton; Köksal, Mümtaz A. (Cancer medicine, 2023)
Total body irradiation (TBI) remains an important component in many conditioning regimens before allogeneic hematopoietic stem cell transplantation (allo-HSCT). Because of its frequent toxicity, patient selection is crucial, making it of interest to identify factors improving engraftment. In this retrospective single center analysis, the characteristics of 48 adult such patients were studied. Mean overall survival (OS) was 22.2 months after allo-HSCT. Interestingly, people with an interval ≥3 days between TBI completion and allo-HSCT showed improved OS, when compared to a shorter interval (p = 0.10). Peripheral blood kinetics after successful engraftment also differed, with a longer interval resulting in a higher platelet count and lower leukocyte and neutrophil (p < 0.05) count. These data suggest that the exact timing of TBI before allo-HSCT might directly impact a patient's survival and could help single out those at higher risk of graft failure who might benefit from an altered conditioning regimen.